Approximation by the Modified $q$-Baskakov-Szász Operators (Analysis in Theory and Applications, 2014)
In this paper we propose the $q$ analogues of modified Baskakov-Szász operators. We estimate the moments and establish direct results in terms of modulus of continuity. An estimate for the rate of convergence and weighted approximation properties of the $q$ operators are also obtained.